2007
DOI: 10.1007/s11244-007-0194-y
|View full text |Cite
|
Sign up to set email alerts
|

High performances of Pt-K/Al2O3 versus Pt-Ba/Al2O3 LNT catalysts in the simultaneous removal of NO x and soot

Abstract: The potentiality of a Pt-K/Al 2 O 3 catalyst in the simultaneous removal of particulate matter (soot) and NO x is investigated in this work by means of Temperature Programmed Oxidation (TPO) experiments and Transient Response Method (TRM), and compared with Pt-Ba/Al 2 O 3 . The results point out the higher performances of K-based sample in the soot combustion as compared to the Ba-based catalyst, and similar behaviour in the NO x -storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 16 publications
3
25
0
Order By: Relevance
“…The features of the reduction of the stored NO x , with NH 3 formation following that of N 2 , were already discussed elsewhere [3,4]. Along with N 2 and NH 3 production, non-negligible amounts of NO and CO 2 are also detected at the reactor outlet.…”
Section: Effect Of the No Inlet Concentrationmentioning
confidence: 75%
See 3 more Smart Citations
“…The features of the reduction of the stored NO x , with NH 3 formation following that of N 2 , were already discussed elsewhere [3,4]. Along with N 2 and NH 3 production, non-negligible amounts of NO and CO 2 are also detected at the reactor outlet.…”
Section: Effect Of the No Inlet Concentrationmentioning
confidence: 75%
“…The Pt-Ba/Al 2 O 3 (1/20/100 w/w) and Pt-K/Al 2 O 3 (1/5.4/ 100 w/w) catalysts used in this study were prepared by incipient wetness impregnation of an alumina support with aqueous solutions of dinitro-diammine platinum, Ba or K acetate [4]. Printex-U (Degussa) was used as model soot, whose properties were well addressed, e.g., in [6,7].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic shift of the temperature window of soot combustion on potassium-promoted spinels in the presence of NO was also reported [23]. It was found that potassium-containing catalysts can be used for the simultaneous removal of NO x and soot [24][25][26], so similar catalytic systems were also investigated in bench-scale experiments [26][27][28].…”
Section: Introductionmentioning
confidence: 99%